The growth and fluorescence of organic monolayers and heterostructures - Kerfoot, James (2018)
Monolayer organic thin films and heterostructures are of great interest for their optical and electronic properties and as systems which allow the interplay between the structural and functional properties of organic molecules to be investigated. In the first experimental section of this thesis, sub-monolayer coverages of perylene tetracarboxylic diimide (PTCDI) were grown on hBN substrates and found to form needle-like monolayer islands at room temperature, while higher growth temperatures gave larger monolayer islands. The molecular packing of monolayer PTCDI was confirmed, using AFM, to correspond to the canted phase. The 0-0 fluorescence peak of this structure was found to occur at 2.208 ± 0.002 eV. The fluorescence of multi-layer PTCDI samples was mapped, with additional peaks measured at 2.135 ± 0.002 eV (580.7 ± 0.5 nm) and 2.118 ± 0.002 eV (585.4 ± 0.5 nm). Relating the morphology and fluorescence of such films using AFM and fluorescence microscopy is a promising way to investigate structural effects on the optical properties of multi-layer organic systems. Using solution deposition techniques, the PTCDI-melamine supramolecular network and the canted phase of PTCDI were deposited on hBN. The molecular packing of both structures was confirmed using AFM and the 0-0 fluorescence peaks were measured to be 2.245 ± 0.002 eV and 2.214 ± 0.002 eV for the PTCDI-melamine network and PTCDI respectively. The fluorescence of sublimed PTCDI, solution deposited PTCDI, PTCDI-melamine and measurements of Me-PTCDI doped helium nano droplets (HND) were compared. A 0.031 ± 0.002 eV red shift was measured from PTCDI-melamine to PTCDI while a 0.346 ± 0.002 eV red shift was measured from doped HND to PTCDI on hBN. A second perylene derivative, perylene tetracarboxylic dianhidride (PTCDA), was also deposited on hBN. Comparing the fluorescence of PTCDA monolayers on various dielectric substrates suggested a large shift due to the coupling of transition dipole moments and image dipoles beneath the dielectric surface. The shift between PTCDI and PTCDI-melamine was attributed to the coupling of transition dipole moments, for which the exciton bandstructure of both phases has been calculated with and without screening. The growth of sublimed C60 was also investigated, with monolayer islands observed for growth at room temperature and faceted bi-layer islands observed at 212 °C. The growth of PTCDI/C60 ¬heterostructures was also investigated, with C60 found to form monolayer islands on monolayer PTCDI at room temperature. At higher growth temperatures, C60 was found to form multilayers, with a reduced island density at PTCDI island edges, suggesting upward and downward hopping from the PTCDI surface to the second C60 layer and hBN respectively. C60 was found to quench the fluorescence of PTCDI and led to a 0.032 ± 0.02 eV blue shift. Finally, the growth of cyanuric acid-melamine (CA.M) on CVD graphene and CA.M/PTCDI heterostructures on hBN was investigated. Cyanuric acid-melamine was found to form monolayers with a honeycomb packing structure on CVD graphene. On monolayers of CA.M, PTCDI was found to form needle-like monolayer islands, the row direction of PTCDI is thought to have an on-axis registry with the substrate. Finally, the fluorescence of CA.M/PTCDI heterostructures on hBN was measured, with a 0.045 ± 0.002 eV blue shift from PTCDI on hBN.